Impact of Comorbidities on Chronic Obstructive Pulmonary Disease Patients - Alam, Nakibul; Yuwen, Xue; Xinghua, Tang; Huanhuan, Li; Yun, Xu; Jiajia, Qu; Uddin, M Jalal (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Many studies were conducted on the subject at home and abroad but there is none in Chattogram region of Bangladesh. To unveil the facts and figures on the subject we have conducted the study. Methods: It was a descriptive study conducted in 2017 at different Private Hospitals of Chattogram. Sample size was purposively determined. Data were collected with a pretested checklist. SPSS version 20 was used for data management. Results: Total 1490 patients were studied. Mean age was 45±6.3 years. Comorbidities were found in 924(62%) cases. Leading comorbidities were Diabetes 66%, Diabetes plus Hypertension 47%, Peptic ulcer diseases 36%, Ischaemic heart disease 15% and others 11%. Chronic Obstructive Pulmonary Disease (COPD) patients with comorbidity stayed longer in hospital (14 days versus 8 days). They also paid more than that of patients without comorbidity (USD 1176 versus 353). Conclusion: COPD with comorbidities cost more than COPD without comorbidities. So, focus should be given more to prevent comorbidities as far as possible. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 8-9